2013
DOI: 10.1089/ars.2011.4487
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nicotinamide Phosphoribosyltransferase Reduces Neutrophil-Mediated Injury in Myocardial Infarction

Abstract: Nampt inhibition appears as a new strategy to dampen CXCL2-induced neutrophil recruitment and thereby reduce neutrophil-mediated tissue injury in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 36 publications
8
75
2
Order By: Relevance
“…21 Thus, beside that fact Evasin-3 treatment did not improve the cerebral levels of specific inflammatory mediators of cerebral injury (such as proteases, TNF, IL-6, and other oxidants), 24,34 the selective reduction in neutrophilic ROS in the presence of Evasin-3 treatment might even be deleterious for the ischemic brain. 20,33 Our results are in partial contrast with previous studies indicating that the abrogation of poststroke neutrophil cerebral infiltration might be a promising therapeutic target to reduce brain injury during reperfusion. 21,35 However, although the majority of the article focused on neutrophil infiltration, less is known on the selective release and expression of neutrophilic products that might increase the cerebral ischemic injury.…”
Section: Evasin-3 Treatment In Ischemic Strokecontrasting
confidence: 99%
See 1 more Smart Citation
“…21 Thus, beside that fact Evasin-3 treatment did not improve the cerebral levels of specific inflammatory mediators of cerebral injury (such as proteases, TNF, IL-6, and other oxidants), 24,34 the selective reduction in neutrophilic ROS in the presence of Evasin-3 treatment might even be deleterious for the ischemic brain. 20,33 Our results are in partial contrast with previous studies indicating that the abrogation of poststroke neutrophil cerebral infiltration might be a promising therapeutic target to reduce brain injury during reperfusion. 21,35 However, although the majority of the article focused on neutrophil infiltration, less is known on the selective release and expression of neutrophilic products that might increase the cerebral ischemic injury.…”
Section: Evasin-3 Treatment In Ischemic Strokecontrasting
confidence: 99%
“…In fact, potent neutrophilic mediators might be differently activated by heart or brain ischemia, suggesting that the reduction in the number of infiltrated neutrophils might not be necessarily related to the degree of their activation. In addition, neutrophils might also indirectly increase (via ROS release) 20 the production of some neuroprotective mediators, such as dibrotyrosine. 21 This endogenous halogenated derivative the aromatic amino acid L-Phenylalanine has been recently shown to protect neurons from ischemic brain injury in rats.…”
Section: Evasin-3 Treatment In Ischemic Strokementioning
confidence: 99%
“…Previous studies showed that intracellular nicotinamide adenine dinucleotide (NAD ϩ IL2, and IL8 (11)(12)(13)(14)(15). In line with these findings, the NAD ϩ -lowering agent FK866 (a nicotinamide phosphoribosyltransferase inhibitor) was shown to have anti-inflammatory activity in mouse models of experimental autoimmune encephalomyelitis, arthritis, polymicrobial sepsis, and heart ischemia (11)(12)(13)15).…”
Section: Cytokine Secretion By Cancer Cells Contributes To Cancer-indmentioning
confidence: 66%
“…In line with this, a recent study reported that Sirt6 acts as a negative regulator of cardiac hypertrophy by repressing IGF/Akt signaling (90). However, in contrast with these results, inhibition of nicotinamide phosphoribosyltransferase, an enzyme involved in NAD synthesis, reduces myocardial infarction by inhibiting neutrophil infiltration and ROS production within the infarcted hearts (91). Interestingly, the same protective phenotype was observed when Sirt6 expression was silenced, implying that although SIRT6 may protect against cardiac hypertrophy, lower SIRT6 levels may be beneficial in the context of myocardial infarction.…”
Section: Cardiovascular Diseasementioning
confidence: 85%